2016
DOI: 10.1038/onc.2016.423
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2-mediated cell death is required for deleting aneuploid cells

Abstract: Caspase-2, one of the most evolutionarily conserved of the caspase family, has been implicated in maintenance of chromosomal stability and tumour suppression. Caspase-2 deficient (Casp2−/−) mice develop normally but show premature ageing-related traits and when challenged by certain stressors, succumb to enhanced tumour development and aneuploidy. To test how caspase-2 protects against chromosomal instability, we utilized an ex vivo system for aneuploidy where primary splenocytes from Casp2−/− mice were expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 54 publications
3
79
0
Order By: Relevance
“…Importantly, cells from mice harboring catalytic-dead caspase-2 (CASP2 C320S ) also show increased aneuploidy following prolonged mitotic arrest 12 . These findings suggest that the activation and enzymatic activity of caspase-2 are required to mediate apoptosis of aneuploid cells.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, cells from mice harboring catalytic-dead caspase-2 (CASP2 C320S ) also show increased aneuploidy following prolonged mitotic arrest 12 . These findings suggest that the activation and enzymatic activity of caspase-2 are required to mediate apoptosis of aneuploid cells.…”
Section: Introductionmentioning
confidence: 99%
“…16 Dawar et al performed time-lapse imaging and cytogenetic analyses of primary splenocytes from Casp2 ¡/¡ mice and CASP2-depleted human cancer cells to show that the absence of CASP2 promoted mitotic slippage as well as the survival of the resulting multinucleated cells that were able to resume proliferation in clonogenic assays. These results suggest that CASP2 may also contribute to SAC signaling, an intriguing hypothesis that requires further confirmation.…”
mentioning
confidence: 99%
“…13 Three recent studies shed light on the mechanism of, and the signal responsible for, CASP2 activation during mitotic catastrophe unveiling the existence of a tight connection between CASP2 and the p53 pathway. [14][15][16] By analyzing colorectal cancers and cell lines displaying high levels of CIN, either at the baseline or upon the pharmacological abrogation of the SAC or increase of replication stress, Lopez-Garcia and colleagues identified a novel mechanism of tolerance to non-diploidy based on the downregulation of CASP2 expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NPM1 and caspase-2 driven apoptosis from the nucleolus could also play a key role in this process, since Kumar and colleagues recently showed that caspase-2 induces apoptosis to remove aneuploid cells. 6 Continued efforts to unravel the contributions of the nucleolar complex to apoptosis or regulation of proliferation will be imperative to determining how caspase-2 protects from aneuploidy.…”
mentioning
confidence: 99%